PENGARUH TERAPI DZIKIR UNTUK MENGURANGI PENYAKIT HATI SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK DI SMK MUHAMMADIYAH 1 PEKANBARU - Azmaliza, Nurul; Umari, Tri; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the effect of dzikir therapy to reduce students' liver disease through group guidance services at SMK Muhammadiyah 1 Pekanbaru. This type of research is quantitative research with experimental methods using the One-Group Pretest-Posttest Design research design. The measuring instrument used in this study was a measurement scale for liver disease students consisting of 52 items before validation, and after validation obtained a valid item number of 35 items with a validity value of 0.507 and reliability of 0.835. The subjects of this study were 7 students who were identified as having high levels of liver disease. The data analysis technique used is non-parametric statistical techniques using the Rank Spearman test. The results of the study proved the research hypothesis was accepted. For that from the Spearman Rank test results obtained Sig (2-tailed) of 0.017, r= 0,714 while the correlation coefficient r2 is 0,509. Thus there is the effect of dzikir therapy on students' liver disease by 51% in SMK Muhammadiyah 1 Pekanbaru. From the Wilcoxon test results obtained (Asymp.Sig) 0.018 <0.05 it can be concluded that there are differences in the scores of liver disease students before and after being given dzikir therapy.Key Words: Dzikir Therapy, Liver Disease,Group Guidance